KUALITAS AIR LAUT DITINJAU DARI INDEKS KEANEKARAGAMAN FITOPLANKTON DI PERAIRAN PANTAI DESA MADAYIN KECAMATAN SAMBELIA KABUPATEN LOMBOK TIMUR - Armiani, Sucika; Harisanti, Baiq Muli (Bioscientist : Jurnal Ilmiah Biologi, 2018)
This study was aimed to riview the quality of sea water in terms of phytoplankton diversity index as the impact of aquaculture shrimp ponds in Madayin village, Sambelia District of East Lombok. This study was conducted in March to June 2018. Sampling was done by purposive sampling method as 6 sampling points was 3 points (stations 4, 5 and 6) were taken from the outlet of sewage shrimp, 1 point (station 3) were taken from estuary, and 2 points (stations 1 and 2) were taken from the sea. Water samples was taken 50 liters and was filtered using 25Î¼m plankton nets. Filtered water put into bottles samples then was preserved by formalin 4%. Phytoplankton analysis was carried out inÂ Biology Laboratory FPMIPA Faculty of Mataram University. Results showed that the diversity index (H) ranged from 2.055 to 2.257, this value indices were moderate/medium. Equitability index (E) value of ranged from moderate to high where the stations 1 and 3 were moderate (0.5 <E <0.75) while stations 2, 4, 5 and 6 were high (E> 0.75). All stations showed that there were no dominance of phytoplankton species. Based on the results, the condition of Madayin coastal was moderate to good condition, no significant ecological pressure.